2019
DOI: 10.1016/j.cmi.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ampC derepression on cefepime MIC in Enterobacterales with chromosomally encoded inducible AmpC β-lactamase

Abstract: ampC derepression cefepime Citrobacter freundii complex Enterobacter cloacae complex Hafnia alvei Klebsiella aerogenes Morganella morganii Providencia spp. Serratia spp. a b s t r a c t Objectives: We aimed to evaluate the effect of ampC derepression on the cefepime MIC in different species of Enterobacterales with chromosomally encoded inducible AmpC b-lactamase.Methods: We analysed a large number of wild-type/mutant pairs (n ¼ 1030 in total). Cefepime MICs were determined by broth microdilution according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, the three principal catalytic motifs that are characteristic for this molecular class ( 64 SXSK, 150 YXN and 315 KTG) are highly conserved, together with at least 70 other residues displaying >90% conservation. Some of these other residues, including 60 F, 61 E, 63 G, 145 G, 148 R, 318 T, 321 G, 322 F, 325 Y and 328 F, are located around the conserved catalytic motifs. Generally, with the exception of a few sequences corresponding 40 to serine hydrolases often identified by BLAST analysis, structural classification should be based on the notion of "genus".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the three principal catalytic motifs that are characteristic for this molecular class ( 64 SXSK, 150 YXN and 315 KTG) are highly conserved, together with at least 70 other residues displaying >90% conservation. Some of these other residues, including 60 F, 61 E, 63 G, 145 G, 148 R, 318 T, 321 G, 322 F, 325 Y and 328 F, are located around the conserved catalytic motifs. Generally, with the exception of a few sequences corresponding 40 to serine hydrolases often identified by BLAST analysis, structural classification should be based on the notion of "genus".…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of transitions between susceptibility and intermediate resistance (S/I) and between susceptibility and resistance (S/R) to cefepime is species-dependent. It is particularly high for the E. cloacae complex (66.3%), non-negligible for H. alvei (36.4%), moderate for Citrobacter and Proteus (18.1-21.9%) and S. marcescens (12.3%), low for K. aerogenes (1.1%) and inexistent for M. morganii (0%) (322). As summarized in Table 5, expansion of the inactivation spectrum results from missense mutations at several mutation hotspots (around triplet 150 YAN, Ω-loop, H10-helix and R2-loop), from duplications or deletions of 2-4 amino acids in the H10 helix (position 293), or insertions of amino acids into the Ω-loop.…”
Section: Acquired Extended-spectrum Cephalosporinases (Esacs)mentioning
confidence: 99%
“…They are intrinsically resistant to aminopenicillin, the combination amoxicillinclavulanic acid, and the first two generations of cephalosporins because they express an inducible ampC cephalosporinase. Under selection pressure, derepressed mutants often emerge, which overproduce cephalosporinase, conferring a high level of resistance to third-generation cephalosporins (3GCs) and increasing the minimum inhibitory concentration required for the fourth generation, such as cefepime (Guérin et al, 2015;Kohlmann et al, 2019;Mizrahi et al, 2020). Since the emergence of extended-spectrum beta-lactamase (ESBL), plasmidic acquisition of ESBL determinants has become an important mechanism in 3GCs resistance (3GC-R), especially among clinical ECC strains, as for most Enterobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AmpC normally does not hydrolyze 4 th generation cephalosporins such as cefepime [195]. However, we observed that MaB1001-1B exhibits less susceptibility to cefepime (MIC=8 µg/mL, intermediate).…”
Section: Phenotypic and Genotypic Cephalosporin-resistance Comparisonmentioning
confidence: 61%